Women's writing in the British Atlantic world :Memory, place and history, 1550-1700 - Chedgzoy, Kate (Cambridge University, 2013)
Kate Chedgzoy explores the ways in which women writers of the early modern British Atlantic world imagined, visited, created and haunted textual sites of memory. Asking how women's writing from all parts of the British Isles and Britain's Atlantic colonies employed the resources of memory to make sense of the changes that were refashioning that world, the book suggests that memory is itself the textual site where the domestic echoes of national crisis can most insistently be heard. Offering readings of the work of poets who contributed to the oral traditions of Wales, Scotland and Ireland, alongside analyses of poetry, fiction and life-writings by well-known and less familiar writers such as Hester Pulter, Lucy Hutchinson, Mary Rowlandson and Aphra Behn, the book explores how women's writing of memory gave expression to the everyday, intimate consequences of the major geopolitical changes that took place in the British Atlantic world in the seventeenth century.